Course of renal allograft function after diagnosis and treatment of post‐transplant lymphoproliferative disorders in pediatric kidney transplant recipients. (22nd May 2021) - Zierhut, Henriette; Kanzelmeyer, Nele; Buescher, Anja; Höcker, Britta; Mauz‐Körholz, Christine; Tönshoff, Burkhard; Metzler, Markus; Pohl, Martin; Pape, Lars; Maecker‐Kolhoff, Britta
Abstract: Background: Post‐transplant lymphoproliferative disease (PTLD) is a life‐threatening complication in renal transplant recipients. Immunomodulatory and chemotherapeutic treatment potentially affect allograft function. The aim of this study was to evaluate graft function of pediatric kidney transplant recipients following diagnosis and standardized treatment of PTLD. Methods: Patients were identified from the German Ped‐PTLD registry, and data on renal function were retrospectively retrieved from patient charts. For PTLD treatment, immunosuppressive therapy was reduced and all children received rituximab (375 mg/m 2 ) for up to six doses. Two patients required additional low‐dose chemotherapy. Renal allograft function was monitored by consecutive measurements of estimated glomerular filtration rate (eGFR) at defined time points. Follow‐up was up to 60 months after PTLD. Results: Twenty patients were included in this cohort analysis. Median time from transplantation to PTLD was 2.4 years. Histopathology showed monomorphic lesions in 16 and polymorphic in 4 patients. Two patients experienced PTLD relapse after 2 and 14 months. Range‐based analysis of variance showed stable allograft function in 17 of 20 patients (85%). Mean eGFR increased during early treatment phase. One patient experienced graft rejection 5.3 years after diagnosis of PTLD. Another patient developed recurrence of primary renal disease (focal‐segmental glomerulosclerosis) and lost his renal allograft 3.8 years post‐transplant (2.0 years after PTLD diagnosis). Conclusion: Treatment of PTLD with rituximab with or without low‐dose chemotherapy in combination with reduced immunosuppression, mostly comprising of an mTOR inhibitor‐based, calcineurin inhibitor‐free regimen, is associated with stable graft function and favorable graft survival in pediatric renal transplant patients.